Civilizing the Police(man): Police Reform, Culture and Practice in Lisbon, c. 1860-1910 - Gonçalves, Cândido Gonçalo Rocha (2012)
This thesis examines the development of a modern urban police force - professional and civil - and its role in the everyday life of the Portuguese capital city, between the start of the city's modern growth in the 1860s and the Republican Revolution of October 1910. It begins by examining the political process of institutional reform during the early 1860s, which led to the creation of Policia Civil de Lisboa in 1867. Using the daily orders of Policia Civil as the anchor source, the thesis concentrates attention on the processes of organizational shaping that marked the development of this police force. The social and cultural diversity within this police force is examined by considering both the rank-file and also the police leadership and the professional specialization that began emerging in the end of the century. But the main focus of this work is on the beat policeman. The thesis examines the organizational strategies devised to 'fabricate' a civilised policeman, as well as their daily enforcement. The evolution of the police's manpower and its deployment throughout the city's territory, together with the arrangement of the working routines, demonstrate that the police increasingly became a central actor in the mediation of social relations in the city. On the part of the population, the growing expectation of the police's availability to intervene was another key factor in the general evolution of the 'idea of police' during this period. Finally, this thesis argues that, while the population became used to 'calling the police', popular criticisms of police actions were also central in the shaping of policing practice.EThOS - Electronic Theses Online ServiceGBUnited Kingdo